ENGLISH TEACHERS INSTRUCTIONAL PRACTICE IN THE PANDEMIC OUTBREAKS: THE EFFORTS AND CHALLENGES - Febi Yolanda Sari; Dewi Suriyani Djamdjuri (Universitas Pahlawan Tuanku Tambusai, 2021)
This research investigates English teachers’ challenges and efforts in instructional practice during the pandemic outbreaks. It aims to know the English teachers’ challenges in the instructional practice during the pandemic outbreaks and to know the English teachers’ efforts during the pandemic outbreaks. The research employed a descriptive qualitative approach and the data was collected through a set of questionnaire and interview. The participants are three English teachers of senior high school. The results show that there are some challenges in instructional practice; the implementation of online learning seems uneven and tends to be teachers centred, less curriculum material coverage, students were not discipline and passive in learning. It has been found also that there are some efforts to overcome the challenges during the pandemic outbreaks such as through the use of recorded videos and create good interactive lesson set to promote students’ critical thinking and encourage the students’ participation in online learning.